The Effectiveness of Flashcards Application to Increase the Students’ Vocabulary of Descriptive Text of the Eighth Grade in SMPN 5 Blitar - Siti Aisyiyah Chaniv Noor Rahmah; Hesty Puspita Sari; Winarsih Winarsih; Supriyono Supriyono (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
The objective of the research is to find out the effectiveness of the use of Flashcards to increase the students’ vocabulary of descriptive text of the eighth grade in SMPN 5 Blitar The design of this research was a quasi-experimental research with a Nonequivalent Control Group Design. The population of this research was the students of SMPN 5 Blitar. The sampling technique in this research is simple random sampling. The sample was 30 students of Class VIII D as the experimental group who was given a new method using flashcards applicationand 25 students of Class VIII E as the control group who was taught using conventional strategies. The research instruments were pre-test and post- test which analyzed by using an independent sample t-test. Furthermore, the result showed that the mean score of the D class that used the Flashcards Application was 80,80, whereas the mean score of the E class that did not use Flashcards was 72.00. the conclusion is the Flashcards application is effective to improve the students’ vocabulary mastery of descriptive text which can be seen in the result of the independent sample t-test, the t test is 4.649 > t table 2.002, then Ha is accepted and H0 is rejected.